2016
DOI: 10.1123/jsm.2015-0230
|View full text |Cite
|
Sign up to set email alerts
|

NBA Primary Market Ticket Consumers: Ex Ante Expectations and Consumer Market Origination

Abstract: We add to the recent ticket market literature by using a unique, disaggregated, and proprietary data set of primary market ticket sales transactions from a National Basketball Association team that includes previously unavailable information on date of purchase, customer location, and other consumer demographics. We find that local and out-of-market fans differ in their total purchase amounts, with out-of-market fans spending more than local consumers, on average, and differential spending effects based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
6
11
1
Order By: Relevance
“…Individual fan utility can be maximized at expected home win probabilities above 50% because attendance at games depends on choices made by both local and out-of-town fans. Again, this is consistent with evidence in Mills, Salaga, and Tainsky (2016).…”
Section: The Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…Individual fan utility can be maximized at expected home win probabilities above 50% because attendance at games depends on choices made by both local and out-of-town fans. Again, this is consistent with evidence in Mills, Salaga, and Tainsky (2016).…”
Section: The Modelsupporting
confidence: 91%
“…Mills, Salaga, and Tainsky () developed evidence supporting this assumption. An analysis of ticket purchase decisions by out‐of‐town fans revealed that spending by out‐of‐town attendees at NBA games increased with the strength of the visiting team, other factors constant.…”
Section: The Modelmentioning
confidence: 94%
“…There did happen to be more users moving through the Wi-Fi funnel at the Amway and Barclays Center compared to the Target Center, possibly associated with the disinterest spectators have for losers and seeking alternative means of stimulation (cf. Mills et al, 2016). Further, the finding that a typical NBA game has approximately 1,000,000 sessions on the venue Wi-Fi network is evidence of its use and role in facilitating the development and diffusion of content from fans in the venue, which has impact for the organization.…”
Section: Discussionmentioning
confidence: 97%
“…These attributes are important to consider as they can impact spectator (dis)interest and the potential use of the venue's Wi-Fi hotspot (cf. Mills et al, 2016) (see Table 2).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation